Electrolytic capacitor and method for manufacturing same
By forming an adhesive portion between the conductive polymer layer and the separator in the electrolytic capacitor, the problem of electrode foil resistance is solved, and capacitor performance with low ESR is achieved.
Patent Information
- Application Number
- CN202380049480.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-28
- Filing Date
- 2023-06-12
- Publication Date
- 2025-02-11
AI Technical Summary
In electrolytic capacitors with low ESR, the resistance portion of the current flows through the electrode foil becomes a problem, especially because the distance from the long end of the foil to the lead terminal of the electrode foil causes an increase in resistance to charge.
By forming a conductive polymer layer in the capacitor element and forming an adhesive portion between the first and second diaphragms, a shorter path of charge is achieved, thereby reducing ESR.
It effectively reduces the equivalent series resistance (ESR) of the electrolytic capacitor and improves the performance of the capacitor.
Smart Images

Figure CN119422216A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an electrolytic capacitor and a method for manufacturing the same. Background Art
[0002] In solid electrolytic capacitors using valve metal foil such as aluminum, instead of the driving electrolyte present in conventional electrolytic capacitors, a conductive polymer with conductivity much higher than that of the driving electrolyte is used to form a solid electrolyte layer between the two electrodes and make it conductive, thereby reducing ESR (equivalent series resistance).
[0003] Typically, the solid electrolyte layer is formed by winding an anode foil and a cathode foil with an anodic oxide film on the surface relative to each other with a separator between them, and the monomer is impregnated in the capacitor element having lead-out parts such as lead terminals on the two valve metal foils, and then the monomer is solidified by polymerization, so that the monomer exists between the two foils.
[0004] For example, 3,4-dialkoxythiophene is used as a monomer, and after adding an acetylene glycol-based surfactant, a polymerization initiator such as iron toluenesulfonate is added in an appropriate amount and heated to polymerize 3,4-dialkoxythiophene. Furthermore, by doping the polymerized 3,4-dialkoxythiophene with a separately polymerized polyanion, a conductive polymer layer with a reduced surface resistivity is formed to form a solid electrolyte layer (for example, refer to Patent Document 1).
[0005] The material of the diaphragm is improved to increase the porosity of the diaphragm, a liquid composition that is a precursor of a conductive polymer is impregnated into the voids of the diaphragm, and the diaphragm is dried or polymerized while maintaining the liquid composition of the conductive polymer, thereby forming a diaphragm layer containing a high-density solid electrolyte layer composed of the conductive polymer (for example, refer to patent document 2).
[0006] On the other hand, as a technology for aluminum electrolytic capacitors aimed at reducing the ESR of products, the following technology has also been developed: a metal plate is connected (bundled) to the end face of the cathode foil at the end face of the aluminum electrolytic capacitor element using a conductive adhesive, and the protruding cathode foils are electrically connected to each other directly via the bundle structure over the end face of the anode foil (for example, refer to Patent Document 3).
[0007] In addition, as a small, large-capacity, and low-ESR (equivalent series resistance) electrolytic capacitor, an electrolytic capacitor comprising an anode foil forming a dielectric layer, a conductive polymer layer with high conductivity formed in a manner covering at least a portion of the dielectric layer, and an electrolyte with the ability to repair the anodic oxide film (at least composed of a solute and a solvent, a liquid with the ability to repair the anodic oxide film and having conductivity) is called a hybrid electrolytic capacitor, and is highly anticipated as an electronic component for vehicle-mounted products. For example, Patent Document 4 describes a method for manufacturing an aluminum electrolytic capacitor in which a dispersion containing a conductive polymer, a polymer dopant, an alkali component, and a solvent is impregnated into a capacitor element, and a portion of the solvent is removed to form a conductive polymer layer.
[0008] Prior art literature
[0009] Patent Literature
[0010] Patent Document 1: Japanese Patent Application Publication No. 2014-40550.
[0011] Patent document 2: Japanese Patent Application Publication No. 2011-91457.
[0012] Patent document 3: Japanese Patent Application Publication No. 2021-519513.
[0013] Patent document 4: International Publication No. 2017 / 090241. Summary of the invention
[0014] Problems to be solved by the invention
[0015] In low ESR electrolytic capacitors, the resistance of current flowing through the electrode foil becomes a problem. Therefore, in capacitor elements, the resistance applied to the charge flowing from the electrode foil to the lead-out portion due to the distance from the end of the long foil of the electrode foil to the lead-out portion such as the lead terminal becomes a problem.
[0016] Therefore, a scheme of forming a metal bundle on the element end face is proposed as shown in Patent Document 3. However, since the bundle itself is made of metal, the dielectric surface of the anode foil may be damaged during formation, and the element surface needs to be processed. In addition, there is a problem that how to maintain insulation between the anode and cathode foils makes the bundle connection complicated, and the cost will also increase.
[0017] The present invention has been made in view of the above-mentioned problems, and an object of the present invention is to provide an electrolytic capacitor capable of achieving sufficiently low ESR and a method for manufacturing the same.
[0018] Technical solutions to the problem
[0019] The electrolytic capacitor of the present invention is characterized in that it has a capacitor element, in which a first diaphragm, an anode foil connected to a lead terminal and having an anodic oxide coating on the surface, a second diaphragm and a cathode foil connected to the lead terminal are arranged in sequence, and a conductive polymer is formed, the first diaphragm and the second diaphragm are respectively protruded from the anode foil in the surface direction and face each other in a state where the first diaphragm and the second diaphragm are respectively electrically connected through the conductive polymer. At least a part of the first diaphragm and the second diaphragm are fixed together to form a bonding portion.
[0020] In the electrolytic capacitor, the bonding portion may be an electrical short-circuit path of the cathode foil.
[0021] In the electrolytic capacitor, the first diaphragm and the second diaphragm may respectively protrude from the anode foil in the surface direction and face each other, and have a protrusion containing the conductive polymer. When the protruding length of the protruding portion of the first diaphragm is set to length a, the protruding length of the protruding portion of the second diaphragm is set to length a', and the thickness of the anode foil at the position where the protruding portions of the first diaphragm and the second diaphragm face each other is set to thickness b, the relationship of length a+length a'≥thickness b holds, and the conductive polymer fixes at least a portion of the protruding portion of the first diaphragm and at least a portion of the protruding portion of the second diaphragm together.
[0022] In the electrolytic capacitor, the length a and the length a′ may each be greater than or equal to 0.2 mm.
[0023] In the electrolytic capacitor, the first diaphragm, the anode foil, the second diaphragm and the cathode foil may be wound together to have a roughly columnar shape, and the first bottom surface of the roughly columnar shape, out of the first bottom surface and the second bottom surface, has the lead terminal connected to the anode foil and the lead terminal connected to the cathode foil.
[0024] In the electrolytic capacitor, the anode foil may be an aluminum foil or an aluminum alloy foil, and the cathode foil may be a valve metal foil, a valve metal alloy foil, or a valve metal foil having a conductive layer formed on a surface thereof.
[0025] In the electrolytic capacitor, a protruding length of the protruding portion of the first diaphragm and the second diaphragm on the second bottom surface may be greater than a protruding length of the protruding portion of the first diaphragm and the second diaphragm on the first bottom surface.
[0026] In the bonding portion of the electrolytic capacitor, at least one of the first diaphragm and the second diaphragm may be inclined with respect to a cylindrical axis of the capacitor element.
[0027] In the electrolytic capacitor, the capacitor element may contain moisture therein.
[0028] In the electrolytic capacitor, the sum of the area covered by the conductive polymer in the exposed portion of the anode foil on the first bottom surface and the area covered by the conductive polymer in the exposed portion of the anode foil on the second bottom surface may be greater than 48% relative to the total area of the exposed portion of the anode foil on the first bottom surface and the second bottom surface.
[0029] In the electrolytic capacitor, an area covered by the conductive polymer in the exposed portion of the anode foil on the first bottom surface may be 45% or more of an area of the exposed portion of the anode foil on the first bottom surface.
[0030] In the electrolytic capacitor, on at least one of the first bottom surface and the second bottom surface, an area of the exposed portion of the anode foil covered by the conductive polymer increases from a central portion toward an outer peripheral portion.
[0031] In the axial direction of the substantially columnar shape of the electrolytic capacitor, the amount of electrolyte per unit area of the first diaphragm and the second diaphragm may be greater on the first bottom surface side and the second bottom surface side than on the center side.
[0032] In the electrolytic capacitor, the conductive polymer layer may be formed by polymerizing a precursor monomer.
[0033] In the electrolytic capacitor, the first separator and the second separator may be at least one selected from cellulose, rayon, and glass fiber.
[0034] In the electrolytic capacitor, the bonding portion may be formed in at least a half region on a side where the lead terminal connected to the cathode foil is located when the capacitor element is viewed from above.
[0035] In the electrolytic capacitor, it may be that the capacitor element is impregnated with an electrolyte, the first diaphragm and the second diaphragm protrude in the surface direction relative to the anode foil and the cathode foil, respectively, and have a protrusion containing the conductive polymer, and when the protrusion length of the protrusion of the first diaphragm is set to length a, the protrusion length of the protrusion of the second diaphragm is set to length a', and the thickness of the anode foil at the position where the protrusions of the first diaphragm and the second diaphragm are opposite to each other is set to thickness b, the relationship of length a+length a'≥thickness b holds, and the conductive polymer bonds at least a portion of the protrusion of the first diaphragm and at least a portion of the protrusion of the second diaphragm together to form a bonding portion.
[0036] In the electrolytic capacitor, the adhesive portion may contain an electrolyte solution and swell to be in a wet state, thereby having adhesiveness.
[0037] In the electrolytic capacitor, the bonding portion may be a structure that is conducted through a short-circuit path of the cathode foil, and between the first diaphragm and the second diaphragm, the bonding portion contains an electrolyte and swells and is in a wet state in a manner that connects the diaphragms to each other, the conductive polymers to each other, or the diaphragm and the conductive polymer, and has adhesiveness.
[0038] In the electrolytic capacitor, the length a and the length a′ may each be greater than or equal to 0.2 mm.
[0039] In the electrolytic capacitor, the first diaphragm, the anode foil, the second diaphragm and the cathode foil may be stacked in sequence and wound together to have a roughly columnar shape, and the first bottom surface of the roughly columnar shape among the first bottom surface and the second bottom surface has the lead terminal connected to the anode foil and the lead terminal connected to the cathode foil.
[0040] In the electrolytic capacitor, the sum of the area covered by the conductive polymer in the end surface of the anode foil on the first bottom surface and the area covered by the conductive polymer in the end surface of the anode foil on the second bottom surface may be greater than 20% relative to the total area of the end surface of the anode foil on the first bottom surface and the second bottom surface.
[0041] In the electrolytic capacitor, an area of the end surface of the anode foil on the first bottom surface covered by the conductive polymer may be 15% or more of an area of the end surface of the anode foil on the first bottom surface.
[0042] In the electrolytic capacitor, in an end surface of the anode foil on at least one of the first bottom surface and the second bottom surface, an area covered by the conductive polymer increases from a center portion toward an outer periphery portion.
[0043] In the electrolytic capacitor, in the axial direction of the substantially columnar capacitor element, the amount of electrolyte per unit area of the first diaphragm and the second diaphragm may be greater on the first bottom surface side and the second bottom surface side than on the center side.
[0044] In the electrolytic capacitor, the conductive polymer layer may be formed of a conductive polymer dispersion having a polymer concentration of 0.5 wt % or more or a viscosity of 10 mPa·s or more.
[0045] In the electrolytic capacitor, the first separator and the second separator may be made of cellulose, rayon, glass fiber, or a mixed paper thereof.
[0046] In the electrolytic capacitor, the bonding portion may be formed at least in any portion of a half region on a side where the lead terminal connected to the cathode foil is located when the capacitor element is viewed from above.
[0047] In the electrolytic capacitor, the adhesive portion may swell when the capacitor element is impregnated with the electrolyte solution and have adhesiveness in a wet state.
[0048] The present invention provides a method for manufacturing an electrolytic capacitor, characterized in that, in a capacitor element in which a first diaphragm, an anode foil connected to a lead terminal and having an anodic oxide coating on the surface, a second diaphragm, and a cathode foil connected to the lead terminal are sequentially arranged, and the first diaphragm and the second diaphragm are respectively protruding from the anode foil in a surface direction and facing each other, a precursor monomer is impregnated into the first diaphragm and the second diaphragm to form a conductive polymer in the capacitor element, and the first diaphragm and the second diaphragm are at least partially fixed together in a state where they are electrically connected through the conductive polymer to form a bonding portion.
[0049] In the manufacturing method of the electrolytic capacitor, it can also be that the first diaphragm and the second diaphragm respectively protrude from the anode foil in the surface direction and are opposite to each other, and have a protrusion containing the conductive polymer. When the protrusion length of the protrusion of the first diaphragm is set to length a, the protrusion length of the protrusion of the second diaphragm is set to length a', and the thickness of the anode foil at the position where the protrusions of the first diaphragm and the second diaphragm are opposite to each other is set to thickness b, the relationship of length a+length a'≥thickness b holds, and the bonding portion is formed between the protrusions of the first diaphragm and the second diaphragm.
[0050] In the method for manufacturing the electrolytic capacitor, when the step of impregnating the capacitor element with the precursor monomer and polymerizing the capacitor element is performed once or repeatedly a plurality of times to form a solid electrolyte layer, the protruding portions of the first and second separators may be simultaneously fixed together to form a bonding portion.
[0051] In the method for manufacturing the electrolytic capacitor, in order to adjust the surface coverage of the bonding portion of the protruding portions of the first and second separators, the bonding portion may be increased by again impregnating or adhering the conductive polymer to the first and second separators to form a solid electrolyte layer.
[0052] In the method for manufacturing the electrolytic capacitor, it may be that, in the capacitor element, when the protruding length of the protruding portion of the first diaphragm is set to length a, the protruding length of the protruding portion of the second diaphragm is set to length a', and the thickness of the anode foil at the portion where the protruding portions of the first diaphragm and the second diaphragm face each other is set to thickness b, the relationship of length a+length a'≥thickness b holds, and the method for manufacturing the electrolytic capacitor includes: a step of forming an adhesive portion between the protruding portions of the first diaphragm and the second diaphragm by impregnating the protruding portions of the first diaphragm and the second diaphragm with a conductive polymer and removing water, thereby connecting the cathode foils to each other or the diaphragm and the cathode foil through a short-circuit path between the protruding portions of the first diaphragm and the second diaphragm; and a step of swelling the conductive polymer forming the adhesive portion and making it wet and adhesive by impregnating the capacitor element with an electrolyte.
[0053] In the method for manufacturing the electrolytic capacitor, the water may be removed by drying.
[0054] In the method for manufacturing the electrolytic capacitor, when impregnating the capacitor element with the electrolyte, the electrolyte may be injected into the conductive polymer to swell the conductive polymer forming the bonding portion to be in a wet state having adhesiveness.
[0055] In the manufacturing method of the electrolytic capacitor, it is also possible that when the conductive polymer is impregnated, the solute is mixed in the dispersion of the conductive polymer and the water is removed, and the dispersion of the conductive polymer is used as the electrolyte, and the electrolyte is impregnated into the capacitor element, so that the conductive polymer forming the bonding portion is swollen and becomes a wet state with adhesiveness.
[0056] In the method for manufacturing the electrolytic capacitor, when the conductive polymer dispersion is used as the electrolytic solution, the electrolytic solution may be further injected into the capacitor element.
[0057] In the method for producing the electrolytic capacitor, when the conductive polymer dispersion liquid is used as the electrolyte solution, at least one solution selected from water and an organic solvent may be used as a solvent of the conductive polymer dispersion liquid.
[0058] In the method for manufacturing the electrolytic capacitor, the organic solvent may be selected from at least one of diol compounds, lactone compounds and sulfolane having a boiling point of 150° C. or higher, and the weight ratio of the organic solvent to water may be 1:99 to 50:50.
[0059] Effects of the Invention
[0060] According to the present invention, it is possible to provide an electrolytic capacitor capable of achieving sufficiently low ESR and a method for manufacturing the same. BRIEF DESCRIPTION OF THE DRAWINGS
[0061] Figure 1 It is a schematic diagram of the electrolytic capacitor according to the first embodiment.
[0062] Figure 2 (a) is a diagram showing the anode foil being unfolded into a sheet. Figure 2 (b) is a diagram showing the cathode foil being unfolded into a sheet. Figure 2 (c) is a diagram showing the first diaphragm being unfolded into a sheet shape.
[0063] Figure 3 This is a diagram showing the cathode foil being unfolded into a sheet.
[0064] Figure 4 (a) is a schematic cross-sectional view for explaining the stacked structure in the capacitor element, Figure 4 (b) is an enlarged cross-sectional view of the anode foil.
[0065] Figure 5 This is a diagram for explaining a structure for forming an adhesive portion between two layers of cathode foil sandwiching an anode foil.
[0066] Figure 6 This is a diagram illustrating a state in which the protrusions are in contact with each other via the anode foil.
[0067] Figure 7 (a) and (b) are diagrams for explaining the effect of forming an adhesive portion along the radial direction on the upper surface of the capacitor element.
[0068] Figure 8 (a) is a diagram illustrating an image of the upper surface of the capacitor element before the conductive polymer is formed, and (b) is a diagram illustrating an image of the upper surface of the capacitor element after the conductive polymer is formed.
[0069] Fig. 9 It is a diagram illustrating the flow of a method for manufacturing the electrolytic capacitor 1 .
[0070] Fig.10 It is a schematic diagram of an electrolytic capacitor according to a second embodiment.
[0071] Fig.11 (a) is a diagram showing the anode foil being unfolded into a sheet. Fig.11 (b) is a diagram showing the cathode foil being unfolded into a sheet. Fig.11 (c) is a diagram showing the first diaphragm being unfolded into a sheet shape.
[0072] Fig.12 This is a diagram showing the cathode foil being unfolded into a sheet.
[0073] Fig.13 (a) is a schematic cross-sectional view for explaining the stacked structure in the capacitor element, Fig.13 (b) is an enlarged cross-sectional view of the anode foil.
[0074] Fig.14 This is a diagram for explaining a structure for forming an adhesive portion between two layers of cathode foil sandwiching an anode foil.
[0075] Fig.15 This is a diagram showing a state where the protrusions are in contact with each other via the anode foil.
[0076] Fig.16 (a) and (b) are diagrams for explaining the effect when an adhesive portion is formed along the radial direction on the upper surface of the capacitor element.
[0077] Fig.17 (a) is a diagram illustrating an image of the upper surface of a capacitor element before forming a conductive polymer. Fig.17 (b) is a diagram illustrating an image of the upper surface of the capacitor element after the conductive polymer is formed.
[0078] Fig.18 This is a diagram illustrating the flow of a method for manufacturing an electrolytic capacitor. DETAILED DESCRIPTION
[0079] Hereinafter, embodiments will be described with reference to the drawings.
[0080] (First Embodiment)
[0081] Figure 1 1 is a schematic diagram of a solid electrolytic capacitor 1 according to the first embodiment. The solid electrolytic capacitor 1 includes a metal case 10 functioning as an exterior body, a capacitor element 20 housed in the metal case 10 , and a sealing body 30 .
[0082] As the metal case 10, a bottomed cylindrical aluminum case having an opening 11 at one end is used. In the present embodiment, the metal case 10 has a cylindrical shape as an example, but may also have a square cylindrical shape.
[0083] The capacitor element 20 has a pair of electrode foils. The pair of electrode foils is an anode foil 21a and a cathode foil 21b. The first diaphragm 22a, the anode foil 21a, the second diaphragm 22b and the cathode foil 21b are stacked in sequence and wound in the length direction to form the capacitor element 20. The shape of the capacitor element 20 is roughly consistent with the internal shape of the metal shell 10. Therefore, the capacitor element 20 has a column shape. The capacitor element 20 in this embodiment is preferably used for a winding type (roughly cylindrical) that can well exert the effect of the short-circuit path in the movement of ions, but can also be used for a stacked capacitor element (roughly square column) formed by stacking anode foils and cathode foils in sequence across a diaphragm.
[0084] As the anode foil 21a and the cathode foil 21b, valve metals such as aluminum, tantalum, titanium, niobium and their alloy foils and vapor-deposited foils can be used. The vapor-deposited film is, for example, a titanium vapor-deposited film. The cathode foil 21b may also be a valve metal foil, an alloy foil of a valve metal, or a foil having a conductive layer formed on the surface of a valve metal. The entire surface of the anode foil 21a is covered with an oxide film. Therefore, the anode foil 21a is insulated from other components. The oxide film functions as a dielectric, and the capacitor element 20 functions as a capacitor. No oxide film is formed on the surface of the cathode foil 21b. In addition, the cathode foil 21b may also form an inorganic layer or a carbon layer on the surface. In this case, the conductive polymer 25 described later is also formed on the surface on which the inorganic layer or the carbon layer is formed.
[0085] Anode foil 21a is connected to anode lead terminal 23a as a lead terminal, and cathode foil 21b is connected to cathode lead terminal 23b as a lead terminal.
[0086] The sealing body 30 is composed of a rubber sealing body having a pair of lead insertion holes 31a and 31b through which the anode lead terminal 23a and the cathode lead terminal 23b are inserted. The sealing body 30 is fitted into the opening 11 of the metal case 10 and is airtightly and firmly attached by a transverse necking groove 12 formed along the outer periphery of the opening 11 by a caulking member or the like. For example, the sealing body 30 is made of butyl rubber or the like.
[0087] In the present embodiment, the bottom surface of each columnar shape formed by capacitor element 20 where the lead terminal is provided is referred to as an upper surface (first bottom surface), and the bottom surface where the lead terminal is not provided is referred to as a lower surface (second bottom surface).
[0088] Figure 2 (a) is a diagram showing anode foil 21a developed into a sheet shape. Figure 2 (b) is a diagram showing the cathode foil 21b being unfolded into a sheet. Figure 2 (a) and Figure 2 As shown in (b), the anode lead terminal 23a and the cathode lead terminal 23b have a structure in which one end side of a metal round bar such as aluminum is punched into a flat plate and a lead is connected to a feather-shaped pole piece terminal portion. The anode foil 21a and the cathode foil 21b are fixedly bonded to the flat plate portion of the pole piece terminal portion. In addition, fixing means drying and solidification, so it is different from bonding.
[0089] Figure 2 (c) is a diagram showing the first separator 22a developed into a sheet. A conductive polymer is formed on the first separator 22a. In the solid electrolytic capacitor 1, no electrolyte solution is used.
[0090] exist Figure 2 In (c) of FIG. 1 , the first diaphragm 22 a is described, but the second diaphragm 22 b also has the same structure as the first diaphragm 22 a .
[0091] The first separator 22a and the second separator 22b are made of at least one material selected from cellulose, rayon, glass fiber and the like.
[0092] The conductive polymer 25 is not particularly limited as long as it is a polymer having conductivity. For example, at least one polymer selected from polythiophene, polypyrrole, polyaniline, and their derivatives is used as the conductive polymer 25. As the conductive polymer 25, polyethylene dioxythiophene (PEDOT) with at least one acid selected from p-toluenesulfonic acid and polystyrenesulfonic acid (PSS) as a dopant is generally used.
[0093] Here, the volume resistivity (Ωm) of the cathode foil 21b and the conductive polymer 25 is described. For example, when aluminum is used as the cathode foil 21b, the volume resistivity of the cathode foil 21b is approximately 2.65×10-6 Ωm. When PEDOT with PSS as a dopant is used as the conductive polymer 25, the volume resistivity of the conductive polymer 25 is 1.0×10 -3 ~1.0×10 -2 about.
[0094] Capacitor element 20 of the present embodiment can achieve high electrostatic capacitance and low ESR by using conductive polymer 25 in addition to cathode foil 21 b. However, ESR may not be sufficiently low. This point will be described in detail.
[0095] Figure 3 and Figure 2 (b) is the same as that of FIG. 2 , which is a diagram showing the cathode foil 21b being unfolded into a sheet. Figure 3 As shown in the example, since electron conduction occurs in the length direction of the cathode foil 21b, the electron conduction distance to the cathode lead terminal 23b sometimes becomes longer. For example, there is a tendency that the distance from the point P farthest from the cathode lead terminal 23b to the cathode lead terminal 23b becomes longer. Therefore, in addition to the thin thickness of the cathode foil, sometimes the resistance from the point P to the cathode lead terminal 23b becomes large, and the ESR cannot become sufficiently low.
[0096] In particular, in a wound capacitor element, since the distance from the foil end to the lead terminal is long and the foil must be wound close to one side, there is a problem that the resistance further increases when charge moves from the foil end farthest from the lead terminal.
[0097] Furthermore, if a cathode having a foil thickness thinner than that of the anode foil and a lower metal purity is used as the cathode, the resistance increases when the metal foil is turned on.
[0098] Therefore, capacitor element 20 of the present embodiment has a structure capable of sufficiently reducing ESR. First, the bonding portion between cathode foils will be described. Figure 4 (a) is a schematic cross-sectional view for explaining the stacked structure in the capacitor element 20. Figure 4 As shown in (a), in cross section, the stacking unit of the first separator 22a, the anode foil 21a, the second separator 22b, and the cathode foil 21b is stacked in this order. The cathode foil 21b is located on the opposite side of the first separator 22a from the anode foil 21a.
[0099] Anode foil 21a has a structure in which an anodic oxide film 212 is formed on the surface of metal foil 211. This anodic oxide film 212 functions as a dielectric. Figure 4As shown in (b), the anode foil 21a is expanded by etching, for example, and an anodic oxide film 212 is formed on the surface by chemical conversion. The expanded anode foil by etching has countless pores on the surface and has a very large surface area. An anodic oxide film 212 is formed on the entire surface of the anode foil 21a with a thickness of 10 to 100 nm. The charge from the cathode lead terminal 23b passes through the cathode foil 21b and charges the anodic oxide film 212 via the conductive polymer of the first diaphragm 22a. However, the charge from the cathode lead terminal 23b passes through the conductive polymer of the first diaphragm 22a. Figure 4 After the cathode foil 21b close to the cathode lead terminal 23b in (a), the cathode foil 21b is passed through the wound cathode foil 21b, and then the cathode foil 21b is passed through the wound cathode foil 21b. Figure 4 The cathode foil 21b in (a) is far from the cathode lead terminal 23b, in order to Figure 4 In (a), the cathode foil 21b on the left side needs to pass through a path of a corresponding length to reach the cathode foil 21b on the right side. If a bonding portion 40 made of a conductive polymer is formed on the separator between the two layers of cathode foil 21b, it is possible to Figure 3 The short circuit is formed on the path from the farthest point P of the cathode lead terminal 23b to the cathode lead terminal 23b described in the figure, which can reduce the ESR. That is, the charge from the cathode lead terminal 23b passes through the cathode foil 21b and charges the anodic oxide film 212 via the conductive polymer. When the charge passes through the cathode foil 21b, if a bonding portion as an electrical short circuit path formed by the conductive polymer is formed between the first diaphragm 22a and the second diaphragm 22b, the charge from the cathode lead terminal 23b reaches the cathode foil 21b at the outer peripheral portion farther from the cathode lead terminal 23b via the bonding portion at a shorter distance, so that the anodic oxide film 212 at the outer peripheral portion is effectively charged from the cathode foil 21b at the outer peripheral portion via the conductive polymer at the outer peripheral portion. As a result, the conductivity of the anode foil 21a at the outer peripheral portion to the anodic oxide film 212 is high, that is, the overall characteristic of the element is low ESR.
[0100] Figure 5 2 is a diagram for explaining a structure for forming a bonding portion between two layers of cathode foil 21b sandwiching anode foil 21a. Figure 5 As shown in the example, in capacitor element 20 of the present embodiment, first diaphragm 22a and second diaphragm 22b protrude from anode foil 21a in the plane direction and face each other. Figure 5 In the example of FIG. 1 , first diaphragm 22 a and second diaphragm 22 b protrude upward from anode foil 21 a on the upper surface of capacitor element 20 .
[0101] The protruding length of the protruding portion 22a1 of the first diaphragm 22a protruding from the anode foil 21a is set as length a. The protruding length of the protruding portion 22b1 of the second diaphragm 22b protruding from the anode foil 21a is set as length a'. The thickness of the anode foil 21a at the position where the protruding portion 22a1 of the first diaphragm 22a and the protruding portion 22b1 of the second diaphragm 22b face each other is set as thickness b. In this case, the relationship of length a+length a'≥thickness b holds.
[0102] Since the first diaphragm 22a and the second diaphragm 22b are flexible, they tend to be easily bent or folded. Figure 6 As shown, the protrusion 22a1 and the protrusion 22b1 are easily in contact with each other through the anode foil 21a. In this case, the conductive polymer 25 of the first diaphragm 22a and the conductive polymer 25 of the second diaphragm 22b are electrically connected by contact. Thus, an adhesive portion 40 is formed between the two layers of cathode foil 21b separated by the anode foil 21a. Thus, the ESR of the capacitor element 20 can be reduced. In addition, by being accommodated in the housing, stress can be applied to the protrusion 22a1 and the protrusion 22b1 to further fix them. That is, in the present embodiment, the adhesive portion 40 is formed by fixing the protrusion 22a1 and the protrusion 22b1 via the conductive polymer 25. In addition, it is preferred that at least one of the protrusion 22a1 and the protrusion 22b1 is tilted relative to the cylindrical axis of the capacitor element 20. For example, it is preferred that at least one of the protrusion 22a1 and the protrusion 22b1 is tilted toward the center of the capacitor element 20. This inclination can suppress the influence of the impact even if the fixed portion is not resistant to the impact.
[0103] Figure 7 (a) and Figure 7 (b) is a diagram for explaining the effect when an adhesive portion is formed along the radial direction on the upper surface of the capacitor element 20. Figure 7 (a) and Figure 7 As shown in (b), anode lead terminal 23a and cathode lead terminal 23b are visible on the upper surface of capacitor element 20. Anode lead terminal 23a and cathode lead terminal 23b are not visible on the lower surface of capacitor element 20.
[0104] like Figure 7 As shown in (a), if no bonding portion is formed, the ion conduction path becomes a path that goes around multiple times and reaches the cathode lead terminal 23b. Figure 7As shown in (b), when the adhesive portion 40 is formed along the radial direction on the upper surface of the capacitor element 20, the short circuit can be repeated, and the path of the cathode lead terminal 23b can be shortened. In addition, in this embodiment, since the insulating anodic oxide film 212 is formed on the anode foil 21a, even if the anode foil 21a contacts the adhesive portion 40, no short circuit will occur.
[0105] Furthermore, from the viewpoint of facilitating contact between the protrusion 22a1 of the first diaphragm 22a and the protrusion 22b1 of the second diaphragm 22b, (length a+length a′) is preferably greater than 1 times the thickness b, and more preferably 2 times or more.
[0106] Similarly, from the viewpoint of making it easy for the protrusion 22a1 of the first diaphragm 22a and the protrusion 22b1 of the second diaphragm 22b to contact each other, the length a and the length a' are preferably 0.2 mm or more, more preferably 0.25 mm or more, and further preferably 0.3 mm or more. For example, the anode foil 21a and the cathode foil 21b have a width of 2.7 mm or more and 7.5 mm in the direction connecting the upper surface and the lower surface of the capacitor element 20. The first diaphragm 22a and the second diaphragm 22b have a width of 3.2 mm or more and 8.0 mm in the direction connecting the upper surface and the lower surface of the capacitor element 20.
[0107] In addition, the bonding portion 40 is preferably formed at a position close to the cathode lead terminal 23b. Therefore, in terms of forming an electrical short-circuit path on the cathode side, it is preferred that the bonding portion 40 is formed in at least a half area (about 1 / 2 of the side where the cathode lead terminal 23b is located) on the capacitor element 20 when viewed from above. Figure 7 The area to the right of the dotted line in (a).
[0108] Furthermore, if the first separator 22a and the second separator 22b are in contact, when the capacitor element 20 is observed from the upper surface side, the exposed portion (end face) of the upper surface side of the anode foil 21a appears to be covered by the conductive polymer 25. The higher the ratio (anode end face coverage) of the upper surface side end face of the anode foil 21a covered by the conductive polymer 25, the more adhesive portions 40 are formed. Therefore, it is preferable to set a lower limit for the anode end face coverage.
[0109] In the present embodiment, the anode end surface coverage of the anode foil 21a can be defined as the ratio of the area covered by the conductive polymer 25 to the exposed area of the anode foil 21a in the upper surface of the capacitor element 20 when the capacitor element 20 is observed from the upper surface side. From the viewpoint of obtaining a sufficient amount of the adhesive portion 40, the anode end surface coverage is preferably 45% or more, more preferably 69% or more, and further preferably 73% or more.
[0110] The anode end surface coverage of anode foil 21a can be calculated by performing image processing based on an image of the upper surface of capacitor element 20 before forming conductive polymer 25 and an image of the upper surface of capacitor element 20 after forming conductive polymer 25. Figure 8 In the image of the upper surface of the capacitor element 20 before the conductive polymer 25 is formed as shown in (a), the area of the exposed portion (end surface) of the anode foil 21a before covering can be calculated by subtracting the area of the first diaphragm 22a, the second diaphragm 22b, the area of the center, the area of the anode lead terminal 23a, the cathode lead terminal 23b, and the area of the cathode foil 21b from the overall area of the capacitor element 20. The area of the center is the area of a circle whose diameter is the longest diameter of the holes in the center when the upper surface of the element is viewed from above, and whose radius is 1 / 2 of the longest diameter of the circle, and the area passing through πr 2 The area calculated by the calculation formula is defined as the area of the center.
[0111] Then, in Figure 8 In the image of the upper surface of the capacitor element 20 after the conductive polymer 25 is formed as illustrated in (b), the area of the exposed portion (end face) of the covered anode foil 21a can be calculated by subtracting the first diaphragm 22a, the second diaphragm 22b, the area of the center portion, the anode lead terminal 23a, the cathode lead terminal 23b, the area of the cathode foil 21b, and the area covered in black by the conductive polymer 25 from the overall area of the capacitor element 20.
[0112] The anode end surface coverage can be calculated by calculating {(area of exposed portion of anode foil 21a before covering)-(ratio of area of exposed portion of anode foil 21a after covering)} / (area of exposed portion of anode foil 21a before covering)×100(%).
[0113] In addition, if Figure 7 As shown in (b), on the upper surface of the capacitor element 20, the distance required for the cathode foil 21b to go around once becomes longer in the outer periphery than in the center. Therefore, on the upper surface of the capacitor element 20, preferably, the area of the exposed portion of the anode foil 21a covered by the conductive polymer 25 increases from the center toward the outer periphery. Here, the increase in the area of the exposed portion of the anode foil 21a covered by the conductive polymer 25 refers to at least one of the following: the absolute value of the area becomes larger, and the area ratio occupied by the conductive polymer 25 in one turn becomes larger.
[0114] exist Figure 5 to Figure 7In (b), the structure of the upper surface of the capacitor element 20 is described, but the lower surface may also be such that the first diaphragm 22a has a protrusion 22a1 protruding toward the lower surface side, and the second diaphragm 22b has a protrusion 22b1 protruding toward the lower surface side. Alternatively, the protrusion 22a1 and the protrusion 22b1 may be provided on only one of the upper surface and the lower surface of the capacitor element 20.
[0115] However, since cathode lead terminal 23b is connected to the upper surface of capacitor element 20 in cathode foil 21b, it is preferable to form an adhesive portion on the upper surface of capacitor element 20. Therefore, it is preferable to have protrusion 22a1 and protrusion 22b1 on the upper surface of capacitor element 20.
[0116] Furthermore, since a plurality of bonding portions are preferably formed on the upper surface side of capacitor element 20 , when protrusions 22 a 1 and 22 b 1 are provided on both the upper surface and the lower surface, length a and length a′ on the upper surface are preferably longer than length a and length a′ on the lower surface.
[0117] In addition, the ratio of the area covered by the conductive polymer 25 to the total area of the exposed portion of the anode foil 21a when the capacitor element 20 is observed from the upper surface side and the exposed portion of the anode foil 21a when the capacitor element 20 is observed from the lower surface side is preferably 48% or more, more preferably 70% or more, and further preferably 73% or more. In addition, the ratio can also be defined as the average value of the anode end surface coverage rate on the upper surface side of the capacitor element 20 and the anode end surface coverage rate on the lower surface side.
[0118] Next, a method for manufacturing electrolytic capacitor 1 will be described. Fig. 9 It is a diagram illustrating the flow of a method for manufacturing the electrolytic capacitor 1 .
[0119] (Production of wound body)
[0120] The first separator 22a, the anode foil 21a connected to the anode lead terminal 23a, the second separator 22b, and the cathode foil 21b connected to the cathode lead terminal 23b are stacked and wound in sequence, and the outer surfaces are fixed with a winding fixing tape to produce a wound body. At this time, the first separator 22a and the second separator 22b are made to protrude further to the upper surface side and the lower surface side than the anode foil 21a.
[0121] (Impregnation and polymerization of conductive polymer)
[0122] Next, the wound body is immersed in a precursor monomer containing water and an organic solvent for 20 minutes in a reduced pressure atmosphere, and then the wound body is lifted from the precursor monomer. In this way, the wound body can be impregnated with the precursor monomer. The oxidant is allowed to act while the remaining precursor monomer remains in the wound body, thereby forming the bonding portion 40.
[0123] For example, after the first separator 22a and the second separator are impregnated with precursor monomers to form a conductive polymer in the capacitor element 20, polymerization is performed while the remaining precursor monomers remain, thereby forming the bonding portion 40. In this case,
[0124] Alternatively, the first diaphragm 22a and the second diaphragm 22b may be impregnated with a precursor monomer, the remaining precursor monomer may be removed, and an oxidant may be allowed to act, thereby causing a polymerization reaction, and then the first diaphragm 22a and the second diaphragm 22b may be impregnated with the precursor monomer again, the remaining precursor monomer may be removed, and an oxidant may be allowed to act, thereby forming the bonding portion 40. By repeating this series of steps, a sufficient amount of bonding portion 40 can be formed. In addition, water may remain inside the capacitor element 20.
[0125] When the process of impregnating the capacitor element 20 with the precursor monomer and polymerizing the capacitor element 20 is repeated once or multiple times to form a solid electrolyte layer, the protruding portions of the first separator 22a and the second separator 22b may be simultaneously fixed to form a bonding portion 40. In order to adjust the surface coverage of the bonding portion 40 of the protruding portions of the first separator 22a and the second separator 22b, the conductive polymer may be impregnated or attached to the first separator 22a and the second separator 22b again to form a solid electrolyte layer to increase the bonding portion.
[0126] (Sealing of capacitor elements)
[0127] Next, the wound body is sealed with metal case 10 and sealing member 30 to complete electrolytic capacitor 1. Thereafter, an aging treatment may be performed while applying a rated voltage.
[0128] According to the manufacturing method of this embodiment, the protrusions 22a1 and the protrusions 22b1 are easily in contact with each other with the anode foil 21a sandwiched therebetween, and the bonding portion 40 is formed between the two layers of the cathode foil 21b sandwiching the anode foil 21a. As a result, the ESR of the capacitor element 20 can be reduced. In addition, when the precursor monomer is impregnated, the diaphragm impregnated with the precursor monomer has adhesiveness, and by allowing the oxidant to act in a state where the diaphragms having adhesiveness are bonded to each other, the precursor monomer is polymerized to form a strong conductive polymer layer integrated with the diaphragm.
[0129] In addition, in the above embodiment, the stacked unit formed by stacking the first separator 22a, the anode foil 21a, the second separator 22b and the cathode foil 21b in sequence is wound, but it is not limited to this. For example, the stacked unit formed by stacking the first separator 22a, the cathode foil 21b, the second separator 22b and the anode foil 21a in sequence may also be wound.
[0130] In the above embodiment, capacitor element 20 has a substantially cylindrical shape, but the present invention is not limited thereto. For example, capacitor element 20 may have another columnar shape such as a square column.
[0131] In the above embodiment, capacitor element 20 is wound, but the present invention is not limited thereto. For example, a plurality of stacked units including first separator 22a, anode foil 21a, second separator 22b, and cathode foil 21b may be stacked without being wound.
[0132] (Second Embodiment)
[0133] Fig.10 1 is a schematic diagram of an electrolytic capacitor 101 according to the second embodiment. The electrolytic capacitor 101 includes a metal case 110 functioning as an exterior body, a capacitor element 120 housed in the metal case 110 , and a sealing body 130 .
[0134] A bottomed cylindrical aluminum case having an opening 111 at one end is used as the metal case 110. In the present embodiment, the metal case 110 has a cylindrical shape as an example, but may also have a square cylindrical shape.
[0135] The capacitor element 120 has a pair of electrode foils. The pair of electrode foils is an anode foil 121a and a cathode foil 121b. The first diaphragm 122a, the anode foil 121a, the second diaphragm 122b and the cathode foil 121b are stacked in sequence and wound in the length direction to form the capacitor element 120. The shape of the capacitor element 120 is roughly consistent with the internal shape of the metal shell 110. Therefore, the capacitor element 120 has a column shape. The capacitor element 120 in the present embodiment is preferably used for a winding type (roughly cylindrical) that can well play the effect of the short-circuit path in the movement of ions, but it can also be used for preparing a pair or more pairs of elements formed by stacking anode foil and cathode foil across a diaphragm and stacking them in sequence. The stacked capacitor element (roughly square column).
[0136] As the anode foil 121a and the cathode foil 121b, valve metals such as aluminum, tantalum, titanium, niobium and their alloy foils and vapor-deposited foils can be used. The anode foil 121a is covered with an anodic oxide film on the entire surface. Therefore, the anode foil 121a is insulated from other components. The capacitor element 120 functions as a capacitor by the anodic oxide film as a dielectric. In addition, the cathode foil 121b can also be formed with an inorganic layer or a carbon layer by vapor deposition or coating on the surface. In this case, the conductive polymer 125 described later is also formed on the surface formed with the inorganic layer or the carbon layer.
[0137] Anode foil 121a is connected to anode lead terminal 123a as a lead terminal, and cathode foil 121b is connected to cathode lead terminal 123b as a lead terminal.
[0138] The sealing body 130 is composed of a rubber sealing body having a pair of lead insertion holes 131a and 131b through which the anode lead terminal 123a and the cathode lead terminal 123b are inserted. The sealing body 130 is fitted into the opening 111 of the metal shell 110 and is airtightly and firmly installed by forming a transverse necking groove 112 along the outer periphery of the opening 111 using a caulking member or the like. For example, the sealing body 130 is made of butyl rubber or the like having a small solvent swelling rate relative to the electrolyte described later. As a result, when the electrolyte contains ethylene glycol, the influence of impurities extracted by ethylene glycol on the capacitor characteristics can be reduced. Specifically, butyl rubber having the characteristics of less than 0.4wt% even when immersed in an ethylene glycol solvent at 125°C for more than 2000 hours, and less than 2wt% even when immersed in a γ-butyrolactone solvent for more than 2000 hours can be used.
[0139] In the present embodiment, among the bottom surfaces of the columnar shape formed by capacitor element 120, the bottom surface on the side where the lead terminal is provided is called an upper surface (first bottom surface), and the bottom surface on the side where the lead terminal is not provided is called a lower surface (second bottom surface).
[0140] Fig.11 (a) is a diagram showing anode foil 121a unfolded into a sheet shape. Fig.11 (b) is a diagram showing the cathode foil 121b being unfolded into a sheet. Fig.11 (a) and Fig.11 As shown in (b), the anode lead terminal 123a and the cathode lead terminal 123b have a structure in which one end of a metal round bar such as aluminum is punched into a flat plate and a lead is connected to a feather-shaped electrode terminal portion. The anode foil 121a and the cathode foil 121b are connected to the flat plate portion of the electrode terminal portion.
[0141] Fig.11 (c) is a diagram showing the first separator 122a developed into a sheet. The first separator 122a is impregnated with an electrolyte solution, and a conductive polymer is formed.
[0142] The positions of the electrolyte impregnation region and the conductive polymer impregnation region in the first diaphragm 122a are not particularly limited. As an example, the electrolyte and the conductive polymer are impregnated in the entire first diaphragm 122a. However, in the axial direction connecting the upper surface and the lower surface of the capacitor element 120, the electrolyte impregnation amount on the upper surface side and the lower surface side is sometimes greater than the electrolyte impregnation amount on the center side of the first diaphragm 122a.
[0143] The conductive polymer 125 tends to be mainly impregnated in the end of the upper surface side and the end of the lower surface side of the capacitor element 120. Therefore, on the axis connecting the upper surface and the lower surface of the capacitor element 120, the impregnation amount of the conductive polymer 125 in the upper surface side and the lower surface side is sometimes greater than the impregnation amount of the conductive polymer 125 on the center side of the first diaphragm 122a. Alternatively, sometimes the conductive polymer 125 is not impregnated on the center side of the first diaphragm 122a, and the conductive polymer 125 is impregnated only on the upper surface side and the lower surface side.
[0144] exist Fig.11 In (c) of FIG. 1 , the first diaphragm 122 a is described, but the second diaphragm 122 b also has the same structure as the first diaphragm 122 a .
[0145] In the present embodiment, the electrolyte 124 can contain polyols, sulfone compounds, lactone compounds, carbonate compounds, diether compounds of polyols, monohydric alcohols, etc. These can be used alone or in combination of two or more.
[0146] The polyol preferably contains at least one of ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, butylene glycol, polyalkylene glycol, and glycerol. As the polyalkylene glycol, polyethylene glycol having an average molecular weight of 200 to 1000 and polypropylene glycol having an average molecular weight of 200 to 5000 are preferably used.
[0147] As the lactone compound, γ-butyrolactone, γ-valerolactone, etc. can be used. As the carbonate compound, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, ethylene carbonate, propylene carbonate, fluoroethylene carbonate, etc. can be contained as a solvent. In particular, ethylene glycol, polyalkylene glycol, γ-butyrolactone, and cyclopentane sulfone are preferably used.
[0148] The electrolyte 124 may contain a solute. As the solute, an acid component, an alkali component, a salt composed of an acid component and an alkali component, a nitro compound, a phenol compound, etc. can be used.
[0149] The acid component can use an organic acid, an inorganic acid, or a composite compound of an organic acid and an inorganic acid. As an organic acid, carboxylic acids such as phthalic acid, isophthalic acid, terephthalic acid, maleic acid, adipic acid, benzoic acid, 4-hydroxybenzoic acid, 1,6-decanedicarboxylic acid, 1,7-octanedicarboxylic acid, and azelaic acid can be used. As an inorganic acid, boric acid, phosphoric acid, phosphorous acid, hypophosphorous acid, phosphoric acid esters, and phosphoric acid diesters can be used.
[0150] As the composite compound of an organic acid and an inorganic acid, borodisalicylic acid, borodiacetic acid, borodiacetic acid, or the like can be used.
[0151] As the base component, primary to tertiary amines, quaternary ammonium, quaternary amidinium, etc. can be used. As primary to tertiary amines, for example, methylamine, dimethylamine, trimethylamine, ethylamine, diethylamine, triethylamine, ethylenediamine, N,N-diisopropylethylamine, tetramethylethylenediamine, hexamethylenediamine, etc. can be used. As quaternary ammonium, for example, tetramethylammonium, triethylmethylammonium, tetraethylammonium, etc. can be used. As quaternary amidinium, for example, ethyldimethylimidazolium, tetramethylimidazolium, etc. can be used.
[0152] In addition, as an absorbent for hydrogen generated inside the capacitor, p-nitrobenzyl alcohol is preferred, and its addition amount is preferably 0.5 to 1.5 wt % in the electrolyte solution. This is because if it is less than 0.5 wt %, the hydrogen absorption effect is small, and on the other hand, if it exceeds 1.5 wt %, the withstand voltage characteristics may be reduced.
[0153] The first separator 122a and the second separator 122b are made of at least one selected from cellulose, rayon, glass fiber, or mixed paper thereof.
[0154] The conductive polymer 125 is not particularly limited as long as it is a polymer having conductivity. For example, at least one polymer selected from polythiophene, polypyrrole, polyaniline, and their derivatives is used as the conductive polymer 125. As the conductive polymer 25, polyethylene dioxythiophene (PEDOT) with at least one acid selected from p-toluenesulfonic acid and polystyrenesulfonic acid (PSS) as a dopant is generally used.
[0155] Here, the volume resistivity (Ωm) of the cathode foil 121b, the electrolyte 124, and the conductive polymer 125 is described. Since the cathode foil 121b is made of metal, it has a lower volume resistivity than the electrolyte 124 and the conductive polymer 125. The conductive polymer 125 also tends to have a lower volume resistivity than the electrolyte 124. For example, when aluminum is used as the cathode foil 121b, the volume resistivity of the cathode foil 121b is approximately 2.65×10 -6 Ωm. When PEDOT with PSS as a dopant is used as the conductive polymer 125, the volume resistivity of the conductive polymer 125 is 1.0×10 -3 ~1.0×10 -2 When ESE2, a product of TAYCA Corporation, is used as the electrolyte 124, the volume resistivity of the electrolyte 124 is about 5×10 3 Ωm (200μS / cm).
[0156] Capacitor element 120 of the present embodiment can achieve high electrostatic capacitance and low ESR by using electrolyte 124 and conductive polymer 125 in combination. However, ESR may not be sufficiently low. This point will be described in detail.
[0157] Fig.12 and Fig.11 (b) is similarly a diagram showing the cathode foil 121b being unfolded into a sheet. Fig.12 As shown in the example, since ion conduction occurs in the length direction of the cathode foil 121b, the ion conduction distance to the cathode lead terminal 123b may become longer. For example, there is a tendency that the distance from the point P farthest from the cathode lead terminal 123b to the cathode lead terminal 123b becomes longer. Therefore, the resistance from the point P to the cathode lead terminal 123b may become larger, and the ESR may not become sufficiently low.
[0158] Therefore, capacitor element 120 of the present embodiment has a structure capable of sufficiently reducing ESR. First, the bonding portion between cathode foils will be described. Fig.13 (a) is a schematic cross-sectional view for explaining the stacked structure in the capacitor element 120. Fig.13 As shown in (a), a stacked unit of a first separator 122a, an anode foil 121a, a second separator 122b, and a cathode foil 121b is stacked in this order in cross section. The cathode foil 121b is located on the opposite side of the first separator 122a from the anode foil 121a.
[0159] Anode foil 121a has a structure in which an anodic oxide film 1212 is formed on the surface of metal foil 1211. This anodic oxide film 1212 functions as a dielectric. Fig.13 As shown in (b), the anode foil 121a is expanded by etching, for example, and an anodic oxide film 1212 is formed on the surface by chemical conversion. The expanded anode foil by etching has countless pores on the surface and has a very large surface area. An anodic oxide film 1212 is formed on the entire surface of the anode foil 121a with a thickness of 10 to 100 nm. The charge from the cathode lead terminal 123b passes through the cathode foil 121b and charges the anodic oxide film 1212 via the conductive polymer or electrolyte of the first diaphragm 122a. However, since the anodic oxide film 1212 has insulating properties, the charge needs to pass through the electrolyte present on the end face of the anode foil 121a in order to reach the second diaphragm 122b adjacent to the anode foil 121a. At this time, the conductivity of the electrolyte present on the end face of the anode foil 121a is about 200μS / cm, so the ESR will increase. If the bonding portion 140 made of a conductive polymer is formed on the separator between the two layers of cathode foil 121b, it is possible to Fig.12The short circuit is formed on the path from the farthest point P of the cathode lead terminal 123b to the cathode lead terminal 123b described in the figure, and the ESR can be reduced. That is, the charge from the cathode lead terminal 123b passes through the cathode foil 121b and charges the anodic oxide film 1212 via the conductive polymer or the electrolyte. When the charge passes through the cathode foil 121b, if a bonding portion as an electrical short circuit path formed by a conductive polymer is formed between the first diaphragm 122a and the second diaphragm 122b, the charge from the cathode lead terminal 123b reaches the cathode foil 121b at the outer peripheral portion farther from the cathode lead terminal 123b via the bonding portion at a shorter distance, and therefore, the anodic oxide film 1212 at the outer peripheral portion is effectively charged from the cathode foil 121b at the outer peripheral portion via the conductive polymer or the electrolyte at the outer peripheral portion. As a result, the electrical conductivity from anode foil 121 a in the outer peripheral portion to anodic oxide film 1212 is high, that is, the characteristics of the entire element become low ESR.
[0160] Fig.14 1 is a diagram for explaining a structure for forming a bonding portion between two layers of cathode foil 121b sandwiching anode foil 121a. Fig.14 As illustrated, in capacitor element 120 of the present embodiment, first diaphragm 122a and second diaphragm 122b protrude from anode foil 121a in the plane direction and face each other. Fig.14 In the example of FIG. 1 , first diaphragm 122 a and second diaphragm 122 b protrude above anode foil 121 a on the upper surface of capacitor element 120 .
[0161] The protruding length of the protruding portion 122a1 of the first diaphragm 122a protruding from the anode foil 121a is set as length a. The protruding length of the protruding portion 122b1 of the second diaphragm 122b protruding from the anode foil 121a is set as length a'. The thickness of the anode foil 121a at the position where the protruding portion 122a1 of the first diaphragm 122a and the protruding portion 122b1 of the second diaphragm 122b face each other is set as thickness b. In this case, the relationship of length a+length a'≥thickness b holds.
[0162] Since the first diaphragm 122a and the second diaphragm 122b are flexible, they tend to be easily bent or folded. Fig.15As shown, the protrusion 122a1 and the protrusion 122b1 are easily in contact with each other through the anode foil 121a. In this case, the conductive polymer 125 of the first diaphragm 122a and the conductive polymer 125 of the second diaphragm 122b are electrically connected by contact. Thus, the bonding portion 140 is formed between the two layers of cathode foil 121b separated by the anode foil 121a. The bonding portion 140 is a structure that conducts with the short-circuit path of the cathode foil 121b, and connects the diaphragms to each other, the conductive polymers to each other, or the diaphragms and the conductive polymers between the first diaphragm 122a and the second diaphragm 122b. Thus, the ESR of the capacitor element 120 can be reduced. In addition, in the process of forming the conductive polymer 125 and impregnating the electrolyte, it can further have the adhesiveness of the conductive polymer, and at this stage, the protrusion 122a1 and the protrusion 122b1 can be spontaneously bonded. Furthermore, by being housed in the housing, stress can be applied to the protrusions 122a1 and 122b1 to further bond them together. That is, in this embodiment, the adhesive portion 140 is formed by bonding the protrusions 122a1 and 122b1 together via the conductive polymer 125 .
[0163] Fig.16 (a) and Fig.16 (b) is a diagram for explaining the effect when an adhesive portion is formed on the upper surface of the capacitor element 120 along the radial direction. Fig.16 (a) and Fig.16 As shown in (b), anode lead terminal 123a and cathode lead terminal 123b are visible on the upper surface of capacitor element 120. Anode lead terminal 123a and cathode lead terminal 123b are not visible on the lower surface of capacitor element 120.
[0164] like Fig.16 As shown in (a), if no bonding portion is formed, the ion conduction path becomes a path that goes around multiple times and reaches the cathode lead terminal 123b. Fig.16 As illustrated in (b), when bonding portion 140 is formed along the radial direction on the upper surface of capacitor element 120, a shortcut can be repeated, and the path to cathode lead terminal 123b can be shortened.
[0165] Furthermore, from the viewpoint of facilitating contact between the protrusion 122a1 of the first diaphragm 122a and the protrusion 122b1 of the second diaphragm 122b, (length a+length a′) is preferably greater than 1 times the thickness b, and more preferably 2 times or more.
[0166] Similarly, from the viewpoint of making it easy for the protrusion 122a1 of the first diaphragm 122a and the protrusion 122b1 of the second diaphragm 122b to contact each other, the length a and the length a' are preferably 0.2 mm or more, more preferably 0.25 mm or more, and further preferably 0.3 mm or more. For example, the anode foil 121a and the cathode foil 121b have a width of 2.7 mm or more and 7.5 mm in the direction connecting the upper surface and the lower surface of the capacitor element 120. The first diaphragm 122a and the second diaphragm 122b have a width of 3.2 mm or more and 8.0 mm in the direction connecting the upper surface and the lower surface of the capacitor element 120.
[0167] In addition, the bonding portion 140 is preferably formed at a position close to the cathode lead terminal 123b. Therefore, when viewed from above relative to the capacitor element 120, the bonding portion 140 is preferably formed at least in the half region ( Fig.16 (a) and Fig.16 Any part of the area to the right of the dotted line in (b).
[0168] Furthermore, if the first diaphragm 122a and the second diaphragm 122b are in contact, when the capacitor element 120 is observed from the upper surface side, the end face portion (end face) of the upper surface side of the anode foil 121a appears to be covered by the conductive polymer 125. The higher the ratio (anode end face coverage) of the upper surface side end face of the anode foil 121a covered by the conductive polymer 125, the more adhesive portions 140 are formed. Therefore, it is preferable to set a lower limit for the anode end face coverage.
[0169] In this embodiment, the anode end surface coverage of the anode foil 121a can be defined as the ratio of the area covered by the conductive polymer 125 relative to the exposed area of the anode foil 121a in the upper surface of the capacitor element 120 when the capacitor element 120 is observed from the upper surface side. From the viewpoint of obtaining a sufficient amount of the bonding portion 140, the anode end surface coverage is preferably 15% or more, more preferably 20% or more, and further preferably 30% or more.
[0170] The anode end surface coverage of anode foil 121a can be calculated by performing image processing based on an image of the upper surface of capacitor element 120 before forming conductive polymer 125 and an image of the upper surface of capacitor element 120 after forming conductive polymer 125. Fig.17In the image of the upper surface of the capacitor element 120 before the conductive polymer 125 is formed as shown in (a), the area of the end face (end face) of the anode foil 121a before covering can be calculated by subtracting the area of the first diaphragm 122a, the second diaphragm 122b, the area of the center, the area of the anode lead terminal 123a, the cathode lead terminal 123b, and the area of the cathode foil 121b from the overall area of the capacitor element 120. The area of the center is the area of a circle whose diameter is the longest diameter of the holes in the center when the upper surface of the element is viewed from above, and whose radius is 1 / 2 of the longest diameter of the circle, and the area passing through πr 2 The area calculated by the calculation formula is defined as the area of the center.
[0171] Then, in Fig.17 In the image of the upper surface of the capacitor element 120 after the conductive polymer 125 is formed as illustrated in (b), the area of the end surface (end face) of the covered anode foil 121a can be calculated by subtracting the first diaphragm 122a, the second diaphragm 122b, the area of the center portion, the anode lead terminal 123a, the cathode lead terminal 123b, the area of the cathode foil 121b, and the area covered in black by the conductive polymer 125 from the overall area of the capacitor element 120.
[0172] The anode end surface coverage can be calculated by calculating {(area of the end surface of the anode foil 121a before covering)-(ratio of the area of the end surface of the anode foil 121a after covering)} / (area of the end surface of the anode foil 121a before covering)×100(%). Alternatively, the anode end surface coverage can also be the ratio of black to the sum of the area of the end surface of the anode foil 121a after covering (white) and the area covered by the conductive polymer 125 (black).
[0173] In addition, if Fig.16 As shown in (b), on the upper surface of the capacitor element 120, the distance required for the cathode foil 121b to go around once becomes longer in the outer periphery than in the center. Therefore, on the upper surface of the capacitor element 120, preferably from the center toward the outer periphery, the area of the end face of the anode foil 121a covered by the conductive polymer 125 increases. Here, the increase in the area of the end face of the anode foil 121a covered by the conductive polymer 125 refers to at least one of the cases where the absolute value of the area becomes larger and the area ratio occupied by the conductive polymer 125 in one turn becomes larger.
[0174] exist Figure 14 to Figure 16In (b), the structure of the upper surface of the capacitor element 120 is described, but the lower surface may also be such that the first diaphragm 122a has a protrusion 122a1 protruding toward the lower surface side, and the second diaphragm 122b has a protrusion 122b1 protruding toward the lower surface side. Alternatively, the protrusion 122a1 and the protrusion 122b1 may be provided on only one of the upper surface and the lower surface of the capacitor element 120.
[0175] However, since cathode lead terminal 123b is connected to the upper surface of capacitor element 120 in cathode foil 121b, bonding portion 140 is preferably formed on the upper surface of capacitor element 120. Therefore, capacitor element 120 preferably has protrusion 122a1 and protrusion 122b1 on the upper surface.
[0176] Furthermore, since a plurality of bonding portions 140 are preferably formed on the upper surface side of capacitor element 120 , when protrusions 122 a 1 and 122 b 1 are provided on both the upper surface and the lower surface, length a and length a′ on the upper surface are preferably longer than length a and length a′ on the lower surface.
[0177] In addition, the ratio of the area covered by the conductive polymer 125 to the sum of the area of the end face of the anode foil 121a when the capacitor element 120 is observed from the upper surface side and the area of the end face of the anode foil 121a when the capacitor element 120 is observed from the lower surface side is preferably 20% or more, more preferably 40% or more, and further preferably 60% or more. In addition, the ratio can also be defined as the average value of the anode end face coverage rate on the upper surface side of the capacitor element 120 and the anode end face coverage rate on the lower surface side.
[0178] Next, a method for manufacturing electrolytic capacitor 101 will be described. Fig.18 1 is a diagram illustrating a flow of a method for manufacturing electrolytic capacitor 101 .
[0179] (Production of wound body)
[0180] The first separator 122a, the anode foil 121a connected to the anode lead terminal 123a, the second separator 122b, and the cathode foil 121b connected to the cathode lead terminal 123b are stacked and wound in sequence, and the outer surface is fixed with a winding fixing tape to produce a wound body. At this time, the first separator 122a and the second separator 122b are made to protrude further to the upper surface side and the lower surface side than the anode foil 121a.
[0181] (Formation of Conductive Polymer Layer)
[0182] Next, the wound body is immersed in a conductive polymer dispersion containing water and an organic solvent for 20 minutes in a reduced pressure atmosphere, and then the wound body is lifted out of the conductive polymer dispersion. In this way, the wound body can be impregnated with the conductive polymer 125. The wound body is dried while the remaining conductive polymer 125 remains in the wound body, thereby forming the adhesive portion 140.
[0183] For example, as the conductive polymer dispersion, it is preferred to use a material having a polymer concentration of 0.5 wt% or more or a viscosity of 10 mPa·s or more at 20° C. This is because, if the polymer concentration of the conductive polymer dispersion is low, when the conductive polymer is impregnated into the element, an amount of conductive polymer sufficient to form an adhesive portion will not remain on the surface of the element, and if the viscosity of the conductive polymer dispersion is low, when the conductive polymer is impregnated into the element, an amount of conductive polymer required for bonding the first diaphragm 122a and the second diaphragm 122b will not remain on the surface of the element.
[0184] (Impregnation of electrolyte)
[0185] Next, in a reduced pressure atmosphere, a predetermined amount of electrolyte is impregnated into the winding body. In addition, the electrolyte may also be mixed with a solute in the conductive polymer dispersion. That is, the conductive polymer dispersion can be used as an electrolyte. In this case, the impregnation of the electrolyte is carried out simultaneously with the impregnation of the conductive polymer. In addition, the solvent of the conductive polymer dispersion may also be a solution selected from water and an organic solvent. In this case, the organic solvent is selected from at least one of a diol compound, a lactone compound and cyclopentane sulfone having a boiling point of 150°C or more, and the weight ratio of the organic solvent to water may also be 1:99 to 50:50. For example, when impregnating the conductive polymer, the conductive polymer dispersion mixed with the solute is impregnated into the winding body, and when the conductive polymer is formed, it becomes a state of being impregnated with the electrolyte. That is, when the conductive polymer is dried and the moisture in the winding body is removed, the organic solvent of the conductive polymer dispersion liquid remains, so the solute dissolved in the organic solvent in the conductive polymer dispersion liquid functions as an electrolyte. Thus, by simultaneously performing the formation of the bonding portion and the impregnation of the electrolyte, the shortening of the manufacturing process can be achieved. In addition, when the conductive polymer dispersion liquid is used as an electrolyte, the additional electrolyte can also be impregnated in the winding body. The impregnation amount of the additional electrolyte amount is preferably more than 2 times and less than 100 times relative to the weight of the electrolyte in the dispersion liquid, and more preferably more than 5 times and less than 20 times. The composition of the additional electrolyte can be the same composition as the electrolyte in the dispersion liquid, or it can be different. For example, the element impregnated with the dispersion liquid as the electrolyte and dehydrated by drying, etc., is immersed in the bath of the additional electrolyte in a manner that the lead terminal is located on the upper side and the part of the winding body is completely immersed, and reduced pressure impregnation is performed, so that the additional electrolyte can be introduced into the interior of the element.
[0186] The reason for impregnation with additional electrolyte is as follows. When the dispersion is used as the electrolyte, since a composite layer of the conductive polymer and the electrolyte is formed during drying, the conductivity of the conductive polymer and the repair of the oxide film near the conductive polymer can be taken into account. On the other hand, regarding the repair of the oxide film near the conductive polymer, as an initial repair amount, the amount of electrolyte in the dispersion is sufficient, but in view of long-term repair, the electrolyte is insufficient. Therefore, in order to form a long-term stable element, it is necessary to impregnate with additional electrolyte. That is, when the conductive polymer dispersion is used as the electrolyte, in order to extend the life of the capacitor, it is particularly effective to inject additional electrolyte.
[0187] (Assembly of capacitors)
[0188] Next, the wound body is sealed by metal case 110 and sealing member 130, thereby completing electrolytic capacitor 101. Thereafter, an aging treatment may be performed while applying a rated voltage.
[0189] According to the manufacturing method of this embodiment, protrusions 122a1 and 122b1 are easily brought into contact with each other via anode foil 121a, and bonding portion 140 is formed between two layers of cathode foil 121b sandwiching anode foil 121a. As a result, ESR of capacitor element 120 can be reduced.
[0190] In addition, by impregnating the conductive polymer with the electrolyte after impregnating the conductive polymer, the conductive polymer 125 forming the bonding portion 140 can be swollen and wetted, so that it has adhesiveness. In this case, the bonding strength of the protrusion 122a1 and the protrusion 122b1 can be improved. In addition, in the diaphragm having at least one end face of the bonding portion, the amount of electrolyte is adjusted to be more per unit area than the diaphragm in the capacitor element, thereby, the bonding portion where the conductive polymer 125 is bonded to each other swells and has long-term adhesiveness. If it is in this swollen state, the bonding of the bonding portion has softness and adhesiveness due to the presence of the electrolyte, so that, for example, the above-mentioned bonding is not easily damaged by the impact when the product is used, and even if the bonding between the diaphragms is released, it can be bonded and continue to maintain the connection.
[0191] In addition, in the above embodiment, the stacked unit formed by stacking the first separator 122a, the anode foil 121a, the second separator 122b and the cathode foil 121b in sequence is wound, but it is not limited to this. For example, the stacked unit formed by stacking the first separator 122a, the cathode foil 121b, the second separator 122b and the anode foil 121a in sequence may also be wound.
[0192] In the above embodiment, the capacitor element 120 has a substantially cylindrical shape, but the present invention is not limited thereto. For example, the capacitor element 120 may have another cylindrical shape such as a square column.
[0193] In the above embodiment, capacitor element 120 is wound, but the present invention is not limited thereto. For example, a plurality of stacked units including first separator 122a, anode foil 121a, second separator 122b, and cathode foil 121b may be stacked without being wound.
[0194] Example
[0195] Next, the electrolytic capacitor of the first embodiment was produced and its characteristics were investigated.
[0196] (Example 1)
[0197] In Example 1, a wound solid electrolytic capacitor (diameter 6.3 mm×length 5.7 mm) having a rated voltage of 63 V and a rated capacitance of 56 μF was produced. A specific method for producing the solid electrolytic capacitor will be described below.
[0198] (Production of wound body)
[0199] The anode lead terminal is connected to the prepared anode foil. The cathode lead terminal is connected to the cathode foil with a conductor layer on the end face and improved coating properties. Then, the first diaphragm, cathode foil, second diaphragm and anode foil are stacked in sequence, wound while the lead terminal is rolled in, and the outer surface is fixed with a winding fixing tape to make a winding body. At this time, the position of the first diaphragm and the second diaphragm is adjusted so that the protruding length a of the first diaphragm and the protruding length a' of the second diaphragm on the upper surface (lead terminal side) of the winding body become 0.35mm. The produced winding body is immersed in an ammonium phosphate aqueous solution, a prescribed voltage is applied to the anode foil, and a chemical conversion treatment is performed again, thereby mainly forming a dielectric layer on the end face of the anode foil. Afterwards, it undergoes a carbonization process, and again undergoes a chemical conversion process and a carbonization process, and then the element is cleaned and dried. The thickness b of the anode foil is 0.125mm.
[0200] (Fabrication of capacitor elements)
[0201] The winding body is immersed in the conductive polymer precursor monomer contained in a specified container for 3 minutes, and then the winding body is lifted from the conductive polymer precursor monomer. At this time, the coverage of the anode terminal surface achieved by the conductive polymer precursor monomer is adjusted to about 96% to 99%. Next, the winding body impregnated with the conductive polymer precursor monomer is dried in a drying furnace for 45 minutes, and the oxidant is impregnated into the dried element at room temperature. After removing the remaining oxidant, polymerization is performed by heating. Then, further heat treatment is performed as needed, and after slow cooling, an aluminum solid electrolytic capacitor element having a conductive polymer layer and an adhesive portion is obtained.
[0202] The images of the upper and lower surfaces of the capacitor element were processed to calculate the coverage of the anode end surfaces of each. The coverage of the anode end surfaces on the upper surface side was 98.8%. The coverage of the anode end surfaces on the lower surface side was 96.1%. The average coverage of the anode end surfaces of the upper and lower surfaces was 97.6%.
[0203] (Sealing of capacitor elements)
[0204] The solid electrolytic capacitor element was sealed to complete the solid electrolytic capacitor. After that, an aging treatment was performed for 1 hour while applying a rated voltage.
[0205] (Example 2)
[0206] A solid electrolytic capacitor was prepared and evaluated in the same manner as in Example 1 except that the coverage of the anode terminal surface by the conductive polymer was adjusted to about 84% to 86% when the conductive polymer was formed.
[0207] The images of the upper and lower surfaces of the capacitor element were processed to calculate the anode terminal surface coverage of each. The anode terminal surface coverage of the upper surface side was 85.7%. The anode terminal surface coverage of the lower surface side was 83.9%. The average of the anode terminal surface coverage of the upper and lower surfaces was 84.8%.
[0208] (Example 3)
[0209] A solid electrolytic capacitor was prepared and evaluated in the same manner as in Example 1 except that the coverage of the anode terminal surface by the conductive polymer was adjusted to about 73 to 75% when the conductive polymer was formed.
[0210] The images of the upper and lower surfaces of the capacitor element were processed to calculate the anode terminal surface coverage of each. The anode terminal surface coverage of the upper surface side was 73.4%. The anode terminal surface coverage of the lower surface side was 74.2%. The average value of the anode terminal surface coverage of the upper and lower surfaces was 73.8%.
[0211] (Example 4)
[0212] The positions of the first separator and the second separator were adjusted so that the protruding length a of the first separator and the protruding length a' of the second separator on the upper surface (lead terminal side) of the winding body were 0.2 mm. When forming the conductive polymer, the coverage of the anode terminal surface achieved by the conductive polymer was adjusted to about 89 to 91%. Other than this, a solid electrolytic capacitor was prepared and evaluated in the same manner as in Example 1.
[0213] The images of the upper and lower surfaces of the capacitor element were processed to calculate the anode terminal surface coverage of each. As a result, the anode terminal surface coverage of the upper surface side was 69.3%. The anode terminal surface coverage of the lower surface side was 70.6%. The average value of the anode terminal surface coverage of the upper and lower surfaces was 70.1%.
[0214] (Example 5)
[0215] An electrolytic capacitor was prepared and evaluated in the same manner as in Example 4 except that the coverage of the anode terminal surface by the conductive polymer was adjusted to about 74 to 77% when the conductive polymer was formed.
[0216] The images of the upper and lower surfaces of the capacitor element were processed to calculate the anode terminal surface coverage of each. As a result, the anode terminal surface coverage of the upper surface side was 54.2%. The anode terminal surface coverage of the lower surface side was 56.8%. The average value of the anode terminal surface coverage of the upper and lower surfaces was 55.5%.
[0217] (Example 6)
[0218] An electrolytic capacitor was prepared and evaluated in the same manner as in Example 4 except that the coverage of the anode terminal surface by the conductive polymer was adjusted to about 68 to 71% when the conductive polymer was formed.
[0219] The images of the upper and lower surfaces of the capacitor element were processed to calculate the anode terminal surface coverage of each. The anode terminal surface coverage of the upper surface side was 45.7%. The anode terminal surface coverage of the lower surface side was 50.4%. The average of the anode terminal surface coverage of the upper and lower surfaces was 48.1%.
[0220] (Comparative Example 1)
[0221] The positions of the first separator and the second separator were adjusted so that the protruding length a of the first separator and the protruding length a' of the second separator on the upper surface (lead terminal side) of the winding body were 0.06 mm. When forming the conductive polymer, the coverage of the anode terminal surface by the conductive polymer was adjusted to about 22 to 25%. Except for this, an electrolytic capacitor was prepared and evaluated in the same manner as in Example 1.
[0222] The images of the upper and lower surfaces of the capacitor element were processed to calculate the respective anode terminal surface coverage. The result showed that the anode terminal surface coverage on the upper surface side was 34.9%. The anode terminal surface coverage on the lower surface side was 32.5%. The average value of the anode terminal surface coverage of the upper and lower surfaces was 33.7%.
[0223] (Comparative Example 2)
[0224] The positions of the first separator and the second separator were adjusted so that the protruding length a of the first separator and the protruding length a' of the second separator on the upper surface (lead terminal side) of the winding body were 0.04 mm. When forming the conductive polymer, the coverage of the anode terminal surface by the conductive polymer was adjusted to about 18 to 21%. Except for this, an electrolytic capacitor was prepared and evaluated in the same manner as in Comparative Example 1.
[0225] The images of the upper and lower surfaces of the capacitor element were processed to calculate the anode terminal surface coverage of each. The anode terminal surface coverage of the upper surface side was 18.2%. The anode terminal surface coverage of the lower surface side was 20.4%. The average value of the anode terminal surface coverage of the upper and lower surfaces was 19.3%.
[0226] (analyze)
[0227] The electrolytic capacitors obtained in Examples 1 to 6 and Comparative Examples 1 and 2 were respectively measured for capacitance and ESR in the following manner: The ESR value (initial ESR value) (mΩ) of the electrolytic capacitor at a frequency of 100 kHz was measured using a four-terminal LCR meter.
[0228] In Example 1, the ESR was 12.7 mΩ. In Example 2, the ESR was 13.3 mΩ. In Example 3, the ESR was 15.8 mΩ. In Example 4, the ESR was 17.2 mΩ. In Example 5, the ESR was 19.4 mΩ. In Example 6, the ESR was 20.8 mΩ. In Comparative Example 1, the ESR was 26.5 mΩ. In Comparative Example 2, the ESR was 31.6 mΩ. Table 1 shows the results.
[0229] [Table 1]
[0230]
[0231] In Comparative Examples 1 and 2, the ESR becomes high. The reason is considered to be as follows: Since the relationship of length a + length a' ≥ thickness b does not hold, the contact between the diaphragms cannot be obtained, and the bonding part formed by the conductive polymer is not formed between the two layers of cathode foil sandwiching the anode foil. In contrast, in Examples 1 to 6, the ESR is lower than that in Comparative Examples 1 and 2. The reason is considered to be as follows: Since the relationship of length a + length a' ≥ thickness b holds, the contact between the diaphragms is obtained, and the bonding part formed by the conductive polymer is formed between the two layers of cathode foil sandwiching the anode foil. In addition, the ESR of Examples 1 to 6 was studied, and it was found that the higher the anode end surface coverage, the lower the ESR. Based on this result, it is believed that the higher the anode end surface coverage, the more bonding parts are formed.
[0232] Next, an electrolytic capacitor according to the second embodiment was produced and its characteristics were examined.
[0233] (Example 7)
[0234] In Example 7, a wound electrolytic capacitor (diameter 10 mm×length 10 mm) having a rated voltage of 63 V and a rated capacitance of 56 μF was produced. A specific method for producing the electrolytic capacitor will be described below.
[0235] (Production of wound body)
[0236] The anode lead terminal is connected to the prepared anode foil. The cathode lead terminal is connected to the cathode foil which has a conductor layer on the end face and has been treated to improve the coating property. Then, the first diaphragm, the cathode foil, the second diaphragm and the anode foil are stacked in sequence, and the lead terminal is wound while being wound, and the outer surface is fixed with a winding fixing tape to produce a wound body. At this time, the positions of the first diaphragm and the second diaphragm are adjusted so that the protruding length a of the first diaphragm and the protruding length a' of the second diaphragm on the upper surface (lead terminal side) of the wound body become 0.35 mm. The produced wound body is immersed in an aqueous ammonium phosphate solution, and a voltage of 143 V is applied to the anode foil while chemical conversion treatment is performed again at 85°C, thereby mainly forming a dielectric layer on the end face of the anode foil. The thickness b of the anode foil is 0.125 mm.
[0237] (Fabrication of capacitor elements)
[0238] Under a reduced pressure atmosphere (80 kPa), the winding body is immersed in an aqueous dispersion of a conductive polymer contained in a specified container for 20 minutes, and then the winding body is lifted from the dispersion. At this time, the coverage of the anode terminal surface achieved by the conductive polymer is adjusted to about 96%. Next, the winding body impregnated with the conductive polymer is dried in a drying oven at 150°C for 60 minutes to allow the conductive polymers of each layer to adhere to each other to form a bonding portion. In this way, a capacitor element with a bonding portion is obtained.
[0239] The images of the upper and lower surfaces of the capacitor element were processed to calculate the anode end surface coverage of each. The anode end surface coverage of the upper surface side was 97.3%. The anode end surface coverage of the lower surface side was 95.4%. The average value of the anode end surface coverage of the upper and lower surfaces was 96.3%.
[0240] (Impregnation of electrolyte)
[0241] In the capacitor element, a predetermined amount of electrolyte is impregnated under a reduced pressure atmosphere (92 kPa), and an adhesive bonding portion is formed by allowing the electrolyte to be present in the bonding portion, and the amount of electrolyte in the diaphragm having at least one end face of the bonding portion is adjusted to be greater per unit area than the diaphragm in the capacitor element. As the electrolyte, ESE2 manufactured by TAYCA is used. As a result, the bonding portion where the conductive polymers are bonded to each other swells and has long-term adhesion.
[0242] (Sealing of capacitor elements)
[0243] The capacitor element impregnated with the electrolyte solution was sealed to complete the electrolytic capacitor, and then an aging treatment was performed at 85° C. for 1 hour while applying a rated voltage.
[0244] (Example 8)
[0245] An electrolytic capacitor was prepared and evaluated in the same manner as in Example 7 except that the coverage of the anode terminal surface by the conductive polymer was adjusted to about 53% when the conductive polymer was formed.
[0246] The images of the upper and lower surfaces of the capacitor element were processed to calculate the anode terminal surface coverage of each. As a result, the anode terminal surface coverage of the upper surface side was 61.2%. The anode terminal surface coverage of the lower surface side was 43.9%. The average value of the anode terminal surface coverage of the upper and lower surfaces was 52.5%.
[0247] (Example 9)
[0248] An electrolytic capacitor was prepared and evaluated in the same manner as in Example 7 except that the coverage of the anode terminal surface by the conductive polymer was adjusted to about 24% when the conductive polymer was formed.
[0249] The images of the upper and lower surfaces of the capacitor element were processed to calculate the anode terminal surface coverage of each. The anode terminal surface coverage of the upper surface side was 28.4%. The anode terminal surface coverage of the lower surface side was 18.8%. The average value of the anode terminal surface coverage of the upper and lower surfaces was 23.6%.
[0250] (Example 10)
[0251] The positions of the first separator and the second separator were adjusted so that the protruding length a of the first separator and the protruding length a' of the second separator on the upper surface (lead terminal side) of the winding body were 0.2 mm. When forming the conductive polymer, the anode terminal surface coverage rate achieved by the conductive polymer was adjusted to about 76%. Except for this, an electrolytic capacitor was prepared and evaluated in the same manner as in Example 7.
[0252] The images of the upper and lower surfaces of the capacitor element were processed to calculate the anode terminal surface coverage of each. The anode terminal surface coverage of the upper surface side was 78.6%. The anode terminal surface coverage of the lower surface side was 72.5%. The average value of the anode terminal surface coverage of the upper and lower surfaces was 75.6%.
[0253] (Example 11)
[0254] An electrolytic capacitor was prepared and evaluated in the same manner as in Example 10 except that the coverage of the anode terminal surface by the conductive polymer was adjusted to about 39% when the conductive polymer was formed.
[0255] The images of the upper and lower surfaces of the capacitor element were processed to calculate the anode terminal surface coverage of each. The anode terminal surface coverage of the upper surface side was 45.6%. The anode terminal surface coverage of the lower surface side was 32.9%. The average value of the anode terminal surface coverage of the upper and lower surfaces was 39.3%.
[0256] (Example 12)
[0257] An electrolytic capacitor was prepared and evaluated in the same manner as in Example 10 except that the coverage of the anode terminal surface by the conductive polymer was adjusted to about 20% when the conductive polymer was formed.
[0258] The images of the upper and lower surfaces of the capacitor element were processed to calculate the anode terminal surface coverage of each. As a result, the anode terminal surface coverage of the upper surface side was 24.7%. The anode terminal surface coverage of the lower surface side was 16.2%. The average value of the anode terminal surface coverage of the upper and lower surfaces was 20.4%.
[0259] (Comparative Example 3)
[0260] The positions of the first separator and the second separator were adjusted so that the protruding length a of the first separator and the protruding length a' of the second separator on the upper surface (lead terminal side) of the winding body were 0.06 mm. When forming the conductive polymer, the coverage of the anode terminal surface by the conductive polymer was adjusted to about 11%. Except for this, an electrolytic capacitor was prepared and evaluated in the same manner as in Example 7.
[0261] The images of the upper and lower surfaces of the capacitor element were processed to calculate the anode terminal surface coverage of each. The anode terminal surface coverage of the upper surface side was 13.9%. The anode terminal surface coverage of the lower surface side was 9.0%. The average value of the anode terminal surface coverage of the upper and lower surfaces was 11.4%.
[0262] (Comparative Example 4)
[0263] An electrolytic capacitor was prepared and evaluated in the same manner as in Comparative Example 3, except that the coverage of the anode terminal surface by the conductive polymer was adjusted to about 8% when the conductive polymer was formed.
[0264] The images of the upper and lower surfaces of the capacitor element were processed to calculate the anode terminal surface coverage of each. As a result, the anode terminal surface coverage of the upper surface side was 9.5%. The anode terminal surface coverage of the lower surface side was 6.4%. The average value of the anode terminal surface coverage of the upper and lower surfaces was 8.0%.
[0265] (analyze)
[0266] For the electrolytic capacitors obtained in Examples 7 to 12 and Comparative Examples 3 and 4, the electrostatic capacitance and ESR value were determined in the following order. The electrostatic capacitance (initial electrostatic capacitance) (μF) of the electrolytic capacitor at a frequency of 120 Hz was measured using a four-terminal LCR meter. The ESR value (initial ESR value) (mΩ) of the electrolytic capacitor at a frequency of 100 kHz was measured using a four-terminal LCR meter.
[0267] In Example 7, the ESR was 9.5 mΩ. In Example 8, the ESR was 10.4 mΩ. In Example 9, the ESR was 12.6 mΩ. In Example 10, the ESR was 13.5 mΩ. In Example 11, the ESR was 14.2 mΩ. In Example 12, the ESR was 18.3 mΩ. In Comparative Example 3, the ESR was 30.7 mΩ. In Comparative Example 4, the ESR was 34.2 mΩ. Table 2 shows the results.
[0268] [Table 2]
[0269]
[0270] In Comparative Examples 3 and 4, the ESR becomes high. The reason is believed to be as follows: Since the relationship of length a + length a' ≥ thickness b does not hold, the contact between the diaphragms cannot be obtained, and the bonding part formed by the conductive polymer is not formed between the two layers of cathode foil sandwiching the anode foil. In contrast, in Examples 7 to 12, the ESR is lower than that in Comparative Examples 3 and 4. The reason is believed to be as follows: Since the relationship of length a + length a' ≥ thickness b holds, the contact between the diaphragms is obtained, and the bonding part formed by the conductive polymer is formed between the two layers of cathode foil sandwiching the anode foil. In addition, the ESR of Examples 7 to 12 was studied, and it was found that the higher the anode end surface coverage, the lower the ESR. Based on this result, it is believed that the higher the anode end surface coverage, the more bonding parts are formed.
[0271] As mentioned above, although the embodiment of the present invention is described in detail, the present invention is not limited to this specific embodiment, and various modifications and changes can be made within the scope of the gist of the present invention described in the claims.
[0272] Description of Reference Numerals
[0273] 1 Electrolytic capacitor
[0274] 10Metal shell
[0275] 11 Opening
[0276] 12 Transverse necking groove
[0277] 20 capacitor elements
[0278] 21a Anode foil
[0279] 21b cathode foil
[0280] 22a First diaphragm
[0281] 22b Second diaphragm
[0282] 23a Anode lead terminal
[0283] 23b cathode lead terminal
[0284] 30 Sealing body
[0285] 31a and 31b are lead wire insertion holes.
Claims
1. An electrolytic capacitor, characterized in that: A capacitor element is provided, wherein a first separator, an anode foil connected to a lead terminal and having an anodic oxide film on the surface, a second separator, and a cathode foil connected to the lead terminal are sequentially arranged, and a conductive polymer is formed. The first separator and the second separator each have the conductive polymer and protrude from the anode foil in a plane direction and face each other. The first separator and the second separator are at least partially fixed together in a state of being electrically connected via the conductive polymer to form a bonding portion.
2. The electrolytic capacitor according to claim 1, characterized in that: The bonding portion is an electrical short-circuit path of the cathode foil.
3. The electrolytic capacitor according to claim 1 or 2, characterized in that: The first separator and the second separator each protrude from the anode foil in a plane direction and face each other, and have a protruding portion containing the conductive polymer. When the protruding length of the protruding portion of the first diaphragm is set to length a, the protruding length of the protruding portion of the second diaphragm is set to length a', and the thickness of the anode foil at the portion where the protruding portions of the first diaphragm and the second diaphragm face each other is set to thickness b, the relationship of length a+length a'≥thickness b holds. The conductive polymer fixes at least a portion of the protrusion of the first separator and at least a portion of the protrusion of the second separator.
4. The electrolytic capacitor according to claim 3, characterized in that: The length a and the length a' are respectively greater than 0.2 mm.
5. The electrolytic capacitor according to claim 1 or 2, characterized in that: The first separator, the anode foil, the second separator, and the cathode foil are wound together to have a substantially cylindrical shape. The first bottom surface of the first bottom surface and the second bottom surface of the substantially columnar shape has the lead terminal connected to the anode foil and the lead terminal connected to the cathode foil.
6. The electrolytic capacitor according to claim 1 or 2, characterized in that: The anode foil is aluminum foil or aluminum alloy foil, The cathode foil is a valve metal foil, a valve metal alloy foil, or a valve metal foil having a conductive layer formed on the surface thereof.
7. The electrolytic capacitor according to claim 3, characterized in that: A protruding length of the protruding portion of the first diaphragm and the second diaphragm on the second bottom surface is greater than a protruding length of the protruding portion of the first diaphragm and the second diaphragm on the first bottom surface.
8. The electrolytic capacitor according to claim 1 or 2, characterized in that: At the bonding portion, at least one of the first diaphragm and the second diaphragm is inclined with respect to a cylindrical axis of the capacitor element.
9. The electrolytic capacitor according to claim 1 or 2, characterized in that: The capacitor element contains moisture inside.
10. The electrolytic capacitor according to claim 5, characterized in that: The sum of the area covered by the conductive polymer in the exposed portion of the anode foil on the first bottom surface and the area covered by the conductive polymer in the exposed portion of the anode foil on the second bottom surface is more than 48% of the total area of the exposed portion of the anode foil on the first bottom surface and the second bottom surface.
11. The electrolytic capacitor according to claim 5, characterized in that: An area covered by the conductive polymer in the exposed portion of the anode foil on the first bottom surface is 45% or more of an area of the exposed portion of the anode foil on the first bottom surface.
12. The electrolytic capacitor according to claim 5, characterized in that: On at least one of the first bottom surface and the second bottom surface, an area of the exposed portion of the anode foil covered by the conductive polymer increases from the center portion toward the outer periphery.
13. The electrolytic capacitor according to claim 5, characterized in that: In the axial direction of the substantially columnar shape, the amount of electrolyte per unit area of the first separator and the second separator is larger on the first bottom surface side and the second bottom surface side than on the center side.
14. The electrolytic capacitor according to claim 1 or 2, characterized in that: The conductive polymer layer is formed by polymerizing precursor monomers.
15. The electrolytic capacitor according to claim 1 or 2, characterized in that: The first separator and the second separator are at least one selected from cellulose, rayon, and glass fiber.
16. The electrolytic capacitor according to claim 1 or 2, characterized in that: The bonding portion is formed in at least a half region of a side where the lead terminal connected to the cathode foil is located when the capacitor element is viewed from above.
17. The electrolytic capacitor according to claim 1, characterized in that: The capacitor element is impregnated with an electrolyte solution. The first separator and the second separator each protrude from the anode foil and the cathode foil in a plane direction and face each other, and have a protruding portion containing the conductive polymer. When the protruding length of the protruding portion of the first diaphragm is set to length a, the protruding length of the protruding portion of the second diaphragm is set to length a', and the thickness of the anode foil at the portion where the protruding portions of the first diaphragm and the second diaphragm face each other is set to thickness b, the relationship of length a+length a'≥thickness b holds. The conductive polymer bonds at least a portion of the protrusion of the first separator and at least a portion of the protrusion of the second separator to form a bonding portion.
18. The electrolytic capacitor according to claim 17, characterized in that: The bonding portion contains an electrolyte and swells to be in a wet state, thereby having adhesiveness.
19. The electrolytic capacitor according to claim 17, characterized in that: The bonding portion is a structure that is connected through a short-circuit path of the cathode foil, and contains an electrolyte and swells and is in a wet state between the first separator and the second separator in a manner that connects the separators to each other, the conductive polymers to each other, or the separator and the conductive polymer, and has adhesiveness.
20. The electrolytic capacitor according to any one of claims 17 to 19, characterized in that: The length a and the length a' are respectively greater than 0.2 mm.
21. The electrolytic capacitor according to claim 17 or 18, characterized in that: The first separator, the anode foil, the second separator, and the cathode foil are sequentially stacked and wound together to have a substantially cylindrical shape. The first bottom surface of the first bottom surface and the second bottom surface of the substantially columnar shape has the lead terminal connected to the anode foil and the lead terminal connected to the cathode foil.
22. The electrolytic capacitor according to claim 21, characterized in that The sum of the area covered by the conductive polymer at the end surface of the anode foil on the first bottom surface and the area covered by the conductive polymer at the end surface of the anode foil on the second bottom surface is greater than 20% of the total area of the end surfaces of the anode foil on the first bottom surface and the second bottom surface.
23. The electrolytic capacitor according to claim 19, characterized in that: An area of the end surface of the anode foil on the first bottom surface that is covered with the conductive polymer is 15% or more of an area of the end surface of the anode foil on the first bottom surface.
24. The electrolytic capacitor according to claim 21, characterized in that In the end surface of the anode foil on at least either the first bottom surface or the second bottom surface, the area covered by the conductive polymer increases from the center portion toward the outer periphery portion.
25. The electrolytic capacitor according to claim 19, characterized in that In the axial direction of the substantially columnar capacitor element, the amount of electrolyte per unit area of the first and second diaphragms is greater on the first bottom surface side and the second bottom surface side than on the center side.
26. The electrolytic capacitor according to any one of claims 17 to 19, characterized in that: The conductive polymer layer is formed of a conductive polymer dispersion having a polymer concentration of 0.5 wt % or more or a viscosity of 10 mPa·s or more.
27. The electrolytic capacitor according to any one of claims 17 to 19, characterized in that: The first separator and the second separator are made of cellulose, rayon, glass fiber or a mixed paper thereof.
28. The electrolytic capacitor according to any one of claims 17 to 19, characterized in that: The bonding portion is formed at least in any portion of a half region on a side where the lead terminal connected to the cathode foil is located when the capacitor element is viewed from above.
29. The electrolytic capacitor according to any one of claims 17 to 19, characterized in that: The adhesive portion swells when the capacitor element is impregnated with the electrolyte solution and has adhesiveness in a wet state.
30. A method for manufacturing an electrolytic capacitor, characterized in that: In a capacitor element, a first separator, an anode foil connected to a lead terminal and having an anodic oxide film on the surface, a second separator, and a cathode foil connected to the lead terminal are sequentially arranged, and the first separator and the second separator are respectively protruded from the anode foil in a plane direction and face each other. The first and second separators are impregnated with a precursor monomer to form a conductive polymer in the capacitor element, and the first and second separators are fixed together at least partially while being electrically connected via the conductive polymer to form a bonding portion.
31. The method for manufacturing an electrolytic capacitor according to claim 30, characterized in that: The first separator and the second separator each protrude from the anode foil in a plane direction and face each other, and have a protruding portion containing the conductive polymer. When the protruding length of the protruding portion of the first diaphragm is set to length a, the protruding length of the protruding portion of the second diaphragm is set to length a', and the thickness of the anode foil at the portion where the protruding portions of the first diaphragm and the second diaphragm face each other is set to thickness b, the relationship of length a+length a'≥thickness b holds. The bonding portion is formed between the protruding portions of the first diaphragm and the second diaphragm.
32. The method for manufacturing an electrolytic capacitor according to claim 30 or 31, characterized in that: When the step of impregnating the capacitor element with the precursor monomer and polymerizing the capacitor element is performed once or repeatedly a plurality of times to form a solid electrolyte layer, the protruding portions of the first separator and the second separator are also fixed together to form a bonding portion.
33. The method for manufacturing an electrolytic capacitor according to claim 30 or 31, characterized in that: In order to adjust the surface coverage of the bonding portion of the protruding portion of the first separator and the second separator, the bonding portion is increased by impregnating or attaching the conductive polymer to the first separator and the second separator again to form a solid electrolyte layer.
34. The method for manufacturing an electrolytic capacitor according to claim 30, wherein: In the capacitor element, when the protruding length of the protruding portion of the first diaphragm is set to length a, the protruding length of the protruding portion of the second diaphragm is set to length a', and the thickness of the anode foil at the portion where the protruding portions of the first diaphragm and the second diaphragm face each other is set to thickness b, the relationship of length a+length a'≥thickness b holds. The manufacturing method of the electrolytic capacitor comprises: A step of impregnating the protruding portions of the first separator and the second separator with a conductive polymer and removing moisture to form an adhesive portion between the protruding portions of the first separator and the second separator, connecting the cathode foils to each other or the separator and the cathode foil via a short-circuit path; and A step of impregnating the capacitor element with an electrolyte solution to swell the conductive polymer forming the bonding portion to be in a wet state having adhesiveness.
35. The method for manufacturing an electrolytic capacitor according to claim 34, characterized in that: The removal of the moisture is carried out by drying.
36. The method for manufacturing an electrolytic capacitor according to claim 34 or 35, characterized in that: When the capacitor element is impregnated with the electrolyte, the electrolyte is injected into the conductive polymer, so that the conductive polymer forming the bonding portion swells and becomes a wet state having adhesiveness.
37. The method for manufacturing an electrolytic capacitor according to claim 34 or 35, characterized in that: During the impregnation of the conductive polymer, a solute is mixed in a dispersion of the conductive polymer and water is removed, the dispersion of the conductive polymer is used as the electrolyte, the electrolyte is impregnated into the capacitor element, and the conductive polymer forming the bonding portion is swollen to become a wet state having adhesiveness.
38. The method for manufacturing an electrolytic capacitor according to claim 34 or 35, characterized in that: When the conductive polymer dispersion is used as the electrolyte, the electrolyte is further injected into the capacitor element.
39. The method for manufacturing an electrolytic capacitor according to claim 34 or 35, characterized in that: When the conductive polymer dispersion liquid is used as the electrolyte, the solvent of the conductive polymer dispersion liquid is at least one selected from water and an organic solvent.
40. The method for manufacturing an electrolytic capacitor according to claim 39, wherein: The organic solvent is selected from at least one of diol compounds, lactone compounds and sulfolane compounds having a boiling point of 150° C. or higher, and the weight ratio of the organic solvent to water is 1:99 to 50:50.
Citation Information
Patent Citations
Method of manufacturing solid electrolytic capacitor
JP2011091457A
Conductive composition and film having coating film
JP2014040550A
CAPACITOR AND METHOD FOR MANUFACTURING CAPACITOR
JP2021519513A
Electrolytic capacitor and method for manufacturing same
WO2017090241A1